Estudio de factibilidad para la implementación de una operadora de turismo, en el cantón La Maná, provincia de Cotopaxi – año 2013 - Vega Villamar, Angel Mauricio (2015)
This "Feasibility Study for the implementation of a Tour Operator in canton Manna province Cotopaxi" is a project that arises according to the needs of the service to offer, this research is intended to assist in the recovery Canton economy and generate jobs and improve the lifestyle of many people. The research is summarized in a situational analysis, which identified the reality on the existence of a tour operator in the city. The theoretical framework describes the theoretical basis of the variables related to the objectives of the research, with the aim of supporting the development of the project, through market research, supply, demand, pricing, promotion among other things established. The technical study, was established size. The location, infrastructure materials, equipment, and organization of the tour operator. The financial economic study and demonstrate the feasibility and viability of investment through the analysis of revenues, expenses, income statement, financial ratios NPV and IRR. Finally, it is pointed conclusions and recommendations arising from the research conducted, especially, the feasibility and sustainability of investment through life established for the project.